Policy implementation as practice? Using social practice theory to examine multi-level governance efforts to decarbonise transport in the United Kingdom - Hampton, S (Elsevier, 2018)
Following the ‘practice turn’ in energy research, increasing attention is being paid to the practices of policy making. However, energy policy implementation remains under-researched. Using auto-ethnographic and extensive interview data, this paper provides a narrative account of ‘Sustainable Routes’: a project offering grants and advice to small business in the UK to reduce their transport-related emissions. The project exemplifies the model of Multi-Level Governance (MLG), implemented by a coalition of actors, across multiple scales. Research data is analysed using practice theory. Building on recent debates over researching large-scale phenomena, the notion of connected situationalism is used to analyse policy implementation as a bundle of practices. ‘Zooming in’ on periods of disruption following project audits, findings trace how tension and conflict arose in the relationships between actors, played out through the changing constellation of meanings, materials and competences. They highlight for example, how the reinterpretation of policy documentation led material elements such as bicycles to become associated with meanings of risk and liability, requiring a new set of competences on behalf of the carriers of practice. This empirical account demonstrates the value of practice theory for analysing multi-actor, multi-scalar research data, and indicates potential for future research on policy implementation.